SOME OBSERVATIONS ON DEHYDRATION AND DRYING OF ERYTHROCYTES FOR SCANNING ELECTRON MICROSCOPY - Y.S. Haddad , F. (The Iraqi Journal of Veterinary Medicine, 1992)
A comparative study on air drying of human erythrocytes for scanning electron microscopy (S E M), between acetone and ethanol for dehydration and drying was carried out, using a quick method. No morphological deformity or artifacts of erythrocytes was observed. More rapid air drying in acetone (3-5 seconds) was noticed as compared to ethanol (20-30 seconds). Acetone was recommended to be used for air drying, in the absence of critical point drying.